The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/bf03190372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability of alpha-methyldopa normal and film tablet formulations after single oral administration in healthy volunteers

Abstract: In a single dose, randomized, cross-over study, with one week of wash-out period, the relative bioavailability of Dopegyt tablets containing 250 mg alpha-methyldopa (AMD) and Presinol film tablets with identical active ingredient content was examined in 24 healthy volunteers. Since technologically two completely different preparations (a film-tablet and a non-film-tablet) having significantly different in vitro dissolution were to be compared, both preparations were compared to a third one, AMD solution (Dopeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Выявление подходов к разработке методик определения нестабильных соединений в плазме было выполнено на примере микофеноловой кислоты (МФК), содержащей в структуре один фенольный гидроксил и в процессе метаболизма образующей О-ацилглюкуронид (АГМФК) и фенольный глюкуронид (ФГМФК) [8,9], деметилированной мебевериновой кислоты (ДМК), также содержащей в структуре один фенольный гидроксил и метаболизирующейся с образованием фенольного глюкуронида (ФГДМК) [22], и метилдопы (МД), содержащей два фенольных гидроксила (рис. 1) [30,32,35,36]. Данные методики разрабатывались для изучения биоэквивалентности (БЭ) лекарственных препаратов данных веществ.…”
Section: Introductionunclassified
“…Выявление подходов к разработке методик определения нестабильных соединений в плазме было выполнено на примере микофеноловой кислоты (МФК), содержащей в структуре один фенольный гидроксил и в процессе метаболизма образующей О-ацилглюкуронид (АГМФК) и фенольный глюкуронид (ФГМФК) [8,9], деметилированной мебевериновой кислоты (ДМК), также содержащей в структуре один фенольный гидроксил и метаболизирующейся с образованием фенольного глюкуронида (ФГДМК) [22], и метилдопы (МД), содержащей два фенольных гидроксила (рис. 1) [30,32,35,36]. Данные методики разрабатывались для изучения биоэквивалентности (БЭ) лекарственных препаратов данных веществ.…”
Section: Introductionunclassified
“…The method used wasvalidated forspecificity, accuracy,precision and sensitivity.The pharmacokineticparameters (C max , AUC 0-t ,AUC 0-1 )werestatisticallycompared byanalysisof variance(ANOVA)for test and referencef ormulations. [4].Although in previous studies,spectrofluorimetric, gasand liquid chromatographicmethodshavebeen reported tobeused fordetermination of a -methyldopa in biologicalf luids [4][5][6], in the presents tudyin which the bioavailability of twotabletformulationsof amethyldopahasbeen compared,the plasmaconcentrationsof methyldopawered etermined using amodified HPLC method withf luorescenced etection. The new HPLC method wasv alidated fors pecificity,a ccuracy, precision and sensitivity.Furthermore,the pharmacokineticparameters of test and referencef ormulations (C max ,A UC 0-t ,A UC 0-1 )werestatisticallycompared by analysisof variance(ANOVA).…”
Section: Introductionmentioning
confidence: 99%